The poly (ADP-ribose) polymerase inhibitor olaparib attenuates established pulmonary fibrosis in a large animal model - Habtamu B. Derseh; Andrew N. Davies; Alarna Young; Sylvie Bischof; Joseph Pelle; David Rudd; Michelle McIntosh; David Piedrafita; Robert J. Bischof (BMC Pulmonary Medicine)
Abstract Background Poly (ADP‒ribose) polymerase (PARP) is a constitutive enzyme involved in regulating various biological processes in health and disease. In the present study, we investigated the role of PARP1 in pulmonary fibrosis and assessed the efficacy of a clinically approved PARP inhibitor, olaparib, for the treatment of pulmonary fibrosis in a large animal bleomycin model. Methods Sheep (n = 12) received two fortnightly instillations of bleomycin (3 U) and saline into separate lung lobes of the same animal. Two weeks after the second bleomycin/saline exposure, sheep were randomly assigned to two groups and treated twice/week orally with either olaparib (10 mg/kg; treated group) or vehicle solution (control group) for four weeks. Olaparib concentrations in plasma were analysed using ultra-high-performance liquid chromatography. The degree of inflammation and fibrosis was assessed using a semiquantitative histopathology scoring method. Masson’s trichrome staining and hydroxyproline assays were used to evaluate collagen deposition in the lungs. We also determined whether olaparib treatment was targeting the migration of sheep lung fibroblasts in vitro using a 2D wound scratch assay. Results Olaparib was rapidly taken up into plasma following oral delivery, returning to baseline levels within 24 h. Therapeutically, olaparib treatment significantly reduced bleomycin-induced PARP1 overexpression and attenuated lung injury and fibrosis. Inflammation and fibrosis scores were significantly lower in bleomycin-injured lobes of sheep treated with olaparib compared to those treated with vehicle only. Additionally, a significant reduction in collagen deposition in the lungs of olaparib-treated sheep compared to vehicle-treated sheep was demonstrated by histopathology and hydroxyproline analyses. In vitro, olaparib significantly inhibited the migration of primary sheep lung fibroblasts. Conclusions Olaparib treatment reduced bleomycin-induced PARP1 overexpression and significantly attenuated established pulmonary fibrosis. Our data suggest that the activation of PARP1 plays a key role in the pathology of pulmonary fibrosis, and provides strong support for the potential repurposing of olaparib and similar PARP inhibitors for the treatment of pulmonary fibrosis.